Effect of gum arabic and fruwash coatings on postharvest quality of summer squash (Cucurbita pepo) - KANNAUJIA, PANKAJ KUMAR; ASREY, RAM; SINGH, AWANI KUMAR; VARGHESE, ELDHO (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was carried out with the aim to find out the beneficial effects of edible coating on postharvest quality of summer squash (Cucurbita pepo L.) under cold storage condition. In our experiments, different edible coatings, viz. gum arabic (5, 10 and 15%) and fruwash were used in order to minimize the excessive moisture loss during postharvest handling and storage. Among the treatments, gum arabic (10%) coating showed better colour retention in terms of Lvalue followed by fruwash treatment. Fruits coated with 10% gum arabic found best for minimizing water loss (more than 50%), respiration rate (≈21%) with higher fruit firmness (7.55 N) as compared with other treatments including control. After 12 days of storage, malondialdehyde content in 10% gum arabic treated fruits (0.141 nmol/g) was recorded significantly lower than control (0.183 nmol/g fruit weight). Highest proline content (235.05 μg/g fruit weight) was recorded in 10% gum arabic while, it was lowest (140.06 μg/g fruit weight) in control. Proline content was ≈68% higher in 10% concentration and ≈30% in 15% gum arabic treated fruit as compared with control after 12th days of storage. Overall 10% gum arabic coated summer squash fruits had better postharvest quality retention characteristics.